1998
DOI: 10.1117/1.601729
|View full text |Cite
|
Sign up to set email alerts
|

Active two-pulse superposition technique of a pulsed Nd:YAG laser

Abstract: In manufacturing processes, various and suitable pulse shapes are required for the purpose of materials processing, and the pulse shape is regarded as a dominant factor according to the specific property of materials. Therefore, this study has undertaken to generate the correct ones by using the two-pulse superposition technique. The pulsed Nd:YAG laser using a multi-mesh inductor L and capacitor C network and the pulse superposition technique is described. We have tried to superpose two pulses with the single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…To obtain high pumping efficiency it is better to use a flashlamp that matches the laser rod dimensions so the required flash lamp parameters are determined using the simulation model and found to be with an arc length of 11 cm and bore diameter of 8 mm [4,5,18]. Design and analysis of pulsed light sources was described by a lot of authors [2][3][4][5][6]. High voltage circuits simulators are not available, so the flashlamp power supply was modeled and simulated using MATLAB SIMULINK.…”
Section: Flash Lampmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain high pumping efficiency it is better to use a flashlamp that matches the laser rod dimensions so the required flash lamp parameters are determined using the simulation model and found to be with an arc length of 11 cm and bore diameter of 8 mm [4,5,18]. Design and analysis of pulsed light sources was described by a lot of authors [2][3][4][5][6]. High voltage circuits simulators are not available, so the flashlamp power supply was modeled and simulated using MATLAB SIMULINK.…”
Section: Flash Lampmentioning
confidence: 99%
“…Nd:YAG media is the most commonly used media of solid-state lasers in many fields. Its popularity has come from its wide range of output powers and the versatile output shapes available from a cw and a pulsed modes [2,3]. Many research efforts directed to study the performance of cw-pumped systems have been reported in details in [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation